Halal Certification, Legal Awareness, and Maqasid al Shari’ah among Fried Chicken MSMEs in Indonesia - Dina Yunita Vintya sari; Lina Kushidayati (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2025)
Abstract: Halal certification for micro and small food enterprises in Indonesia has become a legal obligation and a strategic requirement for Muslim consumer protection. The article examines how the regulatory framework for halal product assurance, the legal awareness and compliance of fried chicken MSMEs, and the normative discourse of Maqāṣid al-Shariah and Fiqh Muʿāmalāt interact in practice. Using a sociological juridical approach, the research combines normative analysis of Undang-Undang Jaminan Produk Halal (Halal Product Assurance Law) and its implementing regulations with qualitative data from observation and indepth interviews with fried chicken MSME owners in Mejobo Village. The findings show that some business actors understand halal certification as both a religious obligation and a business asset that strengthens consumer trust and access to formal markets, yet a significant gap remains between awareness and concrete compliance. Perceptions of procedural complexity and costs, limited socialisation of facilities such as the SeHATI free certification and self declare schemes, weak local supervision, and inconsistent consumer demand for visible halal proof all contribute to the persistence of uncertified operations. Read through Hashim Kamali’s Maqāṣid framework, halal regulation and certification can be seen as instruments for protecting hifz al dīn and hifz al māl, although their actualisation at village level remains partial because institutional wasāʾil do not yet fully match the capacities and conditions of small businesses. The analysis indicates that strengthening halal compliance among MSMEs requires closer alignment between legal design, ethical formation, and community based support within the development of Islamic Business Law in Indonesia. Abstrak: Sertifikasi halal bagi UMKM di sektor pangan di Indonesia telah menjadi kewajiban hukum sekaligus tuntutan strategis bagi perlindungan konsumen Muslim. Artikel ini mengkaji bagaimana kerangka regulasi jaminan produk halal, tingkat kesadaran dan kepatuhan hukum pelaku UMKM ayam goreng, serta wacana normatif Maqāṣid Asy-Syariʿah dan Fikih Muamalah saling berinteraksi dalam praktik. Pendekatan yang digunakan bersifat yuridis sosiologis yang memadukan analisis normatif terhadap Undang-Undang Jaminan Produk Halal dan peraturan pelaksananya dengan data kualitatif hasil observasi dan wawancara mendalam dengan pemilik UMKM ayam goreng di Desa Mejobo, Kudus, Jawa Tengah. Temuan menunjukkan bahwa sebagian pelaku usaha memaknai sertifikasi halal sebagai kewajiban keagamaan sekaligus aset bisnis yang memperkuat kepercayaan konsumen dan membuka akses ke pasar formal, namun masih terdapat jarak yang nyata antara kesadaran dan kepatuhan konkret. Persepsi mengenai kerumitan prosedur dan biaya, terbatasnya sosialisasi fasilitas seperti Sertifikasi Halal Gratis (SeHATI) serta skema pernyataan pelaku usaha (self declare), lemahnya pengawasan di tingkat lokal, dan belum konsistennya tuntutan konsumen terhadap bukti kehalalan yang jelas turut mempertahankan praktik usaha tanpa sertifikat. Jika dibaca melalui perspektif Maqāṣid menurut Hashim Kamali, regulasi dan sertifikasi halal tampak sebagai instrumen perlindungan ḥifẓ al-dīn dan ḥifẓ al-māl, namun aktualisasinya di tingkat desa masih parsial karena wasāʾil (instrument/sarana) kelembagaan belum sepenuhnya sejalan dengan kapasitas dan kondisi usaha kecil, sehingga penguatan kepatuhan halal menuntut keterkaitan yang lebih erat antara desain hukum, pembentukan etika, dan dukungan berbasis komunitas dalam pengembangan Hukum Bisnis Islam di Indonesia.